studying stages of embryonic development and histological structure of aural organ in Nueregus crocatus crocatus L. - Shereen Yaseen Kasim; Ismael Salo Hassan; Hani Malalla Hamodi (College of Education for Pure Sciences, 2009)
ABSTRACT The present study is carried out to investigate the development of the auditory organ in the embryos, Larvae and adults of urodele amphibians Salamander Neurergus crocatus crocatus cope. The study includes the morphology, anatomy and histological structures at the level of light microscope. The development of auditory organ of Neurergus crocatus crocatus initiated at early stages of embryogenesis. The first signals were the appearance of two ectodermal thickenings opposite to the rhombencephalon. These two thickenings were auditory placodes at (24) stage of embryo. The ontogeny of auditory organ continued until at stage (30) at which the auditory pits formed the auditory vesicles and the endolymphatic duct primordium appeared. At late embryonic stages (31-39) characterized by the appearance of endolymphatic sac and elongation of auditory vesicle into tubal form and differentiation of saccules at ventral side and utricle of dorsal side. In addition, the membranous labyrinth is more developed and the horizontal semicircular canal is well identified. At the larval stages (40-49) the macula sacculi and macula utriculi in addition to the anterior, posterior,horizontal, semicircular canals were obvious and their epithelium well developed . At stage 47 the posterior and anterior ampulla,the prospective ear drum,the cochlear primordium well differentiated the metamorphic stage characterized by the differentiation of middle ear from phargngeal pouch and well developed cochlear epithelium.The auditory organ of adult stage includes circumferential cartillagenous capsule envelopes the inner ear, well developed membranous labyrinth, Eustachian tube, ear drum, and columella middle ear very obvious.